2022
DOI: 10.1021/acsomega.2c04665
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interfacial Kinetics and High Rate Performance of LiCoO2 Thin-Film Electrodes by Al Doping and In Situ Al2O3 Coating

Abstract: The structure and surface-interface instability of LiCoO 2 thin-film electrodes during charge–discharge cycles are one of the main factors leading to the deterioration of electrochemical performance. Element doping and surface coating are effective strategies to tackle this issue. In this work, Al-doped and in situ Al 2 O 3 -coated LiCoO 2 composite thin-film electrodes are prepared by magnetron sputtering. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The spectrum can be divided into a peak of 73.3 eV attributed to Al 2 O 3 and a solid solution peak located at ~71.2 eV, indicating that Al 3+ ions exist in both Al 2 O 3 form and solid solution form in LCAO. The O 1s spectra can be divided into two peaks around ~529.5 eV and 532 eV (Figure 3d), respectively, corresponding to the bonds in metallic oxygen bond (Co−O) and nonmetallic oxygen bond (C=O/C−O) forms, [10a,14] respectively. After fitting, it is found that the proportion of the former increases gradually and then decreases when the temperature rises to 950 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum can be divided into a peak of 73.3 eV attributed to Al 2 O 3 and a solid solution peak located at ~71.2 eV, indicating that Al 3+ ions exist in both Al 2 O 3 form and solid solution form in LCAO. The O 1s spectra can be divided into two peaks around ~529.5 eV and 532 eV (Figure 3d), respectively, corresponding to the bonds in metallic oxygen bond (Co−O) and nonmetallic oxygen bond (C=O/C−O) forms, [10a,14] respectively. After fitting, it is found that the proportion of the former increases gradually and then decreases when the temperature rises to 950 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminum and copper are the most studied elements among the existing studies on the influence of impurities in the battery recycling process, because they are current collectors and are most likely to remain in the cathode materials after being broken and separated. Aluminum is generally regarded as a beneficial element and is used as a dopant in many studies to improve the high-voltage performance of cathodes . The used compounds include alumina, aluminum fluoride, LiAlH 4 , etc.…”
Section: Recovery System Based On Direct Recycling Methodsmentioning
confidence: 99%
“…Aluminum is generally regarded as a beneficial element and is used as a dopant in many studies to improve the high-voltage performance of cathodes. 302 The used compounds include alumina, 303 aluminum fluoride, 304 LiAlH 4 , 305 etc. Aluminum element can form a coating layer on the surface of the cathode particles and resist the erosion of fluorine-containing compounds in the electrolyte, thus prolonging the lifespan of the cathode.…”
Section: Recovery System Based On Direct Recycling Methodsmentioning
confidence: 99%
“…The Al 2p core level spectrum (Figure 4c) consists of a peak at about 74.5 eV that is close to the binding energy of Al 3+ in LiAlO 2 . 51 In addition, a shakeup peak located at about 79.2 eV is also present due to defects present in the lattice. 52,53 The deconvoluted Li 1s spectra, shown in Figure 4d,e, are fitted with two peaks located at ∼54.3 and ∼55.6 eV, which confirm the existence of lithium in two different cation environments (i.e., the octahedral Cr 3+ polyhedra and the interstitial Cr 6+ tetrahedra, respectively) in the lattice.…”
Section: Xps and Icp Analysismentioning
confidence: 99%